صلاحيات رئيس الجمهورية في الحالة الاستثنائية في ظل التعديل الدستوري 2020 - أدم بوسالم (My University, 2023)
Summary of the thesis: The constitutional founder granted many powers to the President of the Republic during exceptional circumstances by making him single with the power to declare exceptional cases that fall according to severity from a state of siege to a state of emergency to an exceptional state and finally a state of general mobilization and a state of war. However, the authority of the President of the Republic to approve these cases is not an absolute authority. Rather, it is restricted by many objective and formal conditions that he must respect in order for his decision to declare a case to be a constitutional decision. The constitutional founder worked through the 2020 Constitutional Amendment to further restrict the powers of the President of the Republic by including some formal conditions and adding a time limit of thirty days for the state of emergency and siege and sixty days for the exceptional case, and this is what made the Constitutional Amendment 2020 enjoy a distinguished position. The limitation of the period is considered an essential condition and a real guarantee so that the President of the Republic will not be arbitrary through his discretion in determining the period he deems appropriate, especially since Algeria witnessed the application of a state of emergency for a period of 11 years. The President of the Republic also enjoys the authority to administer the system of exceptional cases through his regulatory authority, which does not pose any problem as long as he is the owner of this authority even in normal cases, in addition to the power of exceptional legislation through the orders conferred upon him constitutionally under Article 142 of the Constitution, and in addition to the legislative jurisdiction he exercises The President of the Republic has exceptional judicial powers that are not expressly stipulated in the constitution, but rather he exercises them according to organizational decrees, which are represented in taking measures of a judicial nature that are supposed to be within the jurisdiction of the judicial authority, and his jurisdiction in exceptional cases extends beyond that by establishing an exceptional judiciary. ........................................ ملخص المذكرة : منح المؤسس الدستوري العديد من الصلاحيات لرئيس الجمهورية خلال الظروف الاستثنائية بإفراده بسلطة إعلان الحالات الاستثنائية التي تندرج حسب الخطورة من حالة الحصار إلى حالة الطوارئ إلى الحالة الاستثنائية و أخيرا حالة التعبئة العامة ‏و حالة الحرب غير أن سلطة رئيس الجمهورية في إقرار هذه الحالات ليست سلطة مطلقة بل مقيدة بالعديد من الشروط الموضوعية و الشكلية التي يتعين عليه احترامها ‏حتى يكون قراره في إعلان إحدى الحالات قرار دستوري . ‏لقد عمل المؤسس الدستوري من خلال التعديل الدستوري 2020 على تقييد سلطات رئيس الجمهورية أكثر من خلال إدراج بعض الشروط الشكلية و إضافة قيد المدة الزمنية المحددة ب ثلاثين يوما لحالة الطوارئ و الحصار و ستين يوما للحالة الاستثنائية و هذا ما جعل التعديل الدستوري 2020 يتمتع بمكانة مميزة حيث يعتبر قيد المدة شرط جوهري و ضمان حقيقي حتى لا يتعسف رئيس الجمهورية من خلال سلطته التقديرية في تحديد المدة التي يراها خاصة و أن الجزائر شهدت تطبيق حالة الطوارئ لمدة 11 سنة . ‏كما يتمتع رئيس الجمهورية بسلطة إدارة نظام الحالات الاستثنائية من خلال سلطته التنظيمية التي لا تطرح أي إشكال مادام هو صاحب هذه السلطة حتى في الحالات العادية بالإضافة إلى صلاحية التشريع الاستثنائي عن طريق الأوامر المخولة له دستوريا بموجب المادة 142 من الدستور ، و إضافة إلى الاختصاص التشريعي يمارس رئيس الجمهورية اختصاصات قضائية استثنائية لم ينص عليها الدستور صراحة و إنما يمارسها بموجب مراسيم تنظيمية و تتمثل في اتخاذ تدابير ذات طابع قضائي و التي من المفروض هي من اختصاص السلطة القضائية كما يمتد اختصاصه في الحالات الاستثنائية إلى أبعد من ذلك بإنشاء قضاء استثنائي . ............................... Résumé de la thèse : Le constituant algérien a accordé de nombreux pouvoirs au président de la République lors des circonstances exceptionnelles en lui attribuant seul le pouvoir de déclarer le cas d’exception qui varie selon la gravité de la situation entre l'état de siège , l'état d'urgence , l'état d'exception et enfin l'état de la mobilisation générale et de l'état de guerre. Né au m’oint , l’autorité du Président de la République pour approuver ces cas n'est pas une autorité absolue, elle est plutôt limitée par de nombreuses conditions de fonds et de formes dont il doit respecter pour que sa décision soit conforme à la constitution. Le constituant algérien à essayé à travers l'amendement constitutionnel de 2020 de restreindre davantage les pouvoirs du président de la République en incluant certaines conditions formelles et en ajoutant un délai de 30 jours pour l'état d'urgence et de siège , ainsi que 60 jours pour l’état exception, cette détermination constitue une vraie garantie devant un éventuel abus de la part du président de la république , d'autant plus que L'Algérie a connu l'application de l'état d'urgence pour une durée de 11 ans. Le président de la république jouit également du pouvoir réglementaire durant l’état d’exception des cas exceptionnels à travers son autorité de régulation, ce qui ne pose aucun problème tant qu'il est titulaire de cette autorité même durant les circonstances ordinaires en plus du pouvoir de légiférer par ordonnances en vertu de l'article 142 de la Constitution. D’un autre coté , le Président de la République exerce des pouvoirs judiciaires exceptionnels qui ne sont pas expressément prévus par la Constitution, mais en vertu de décrets réglementaires, ces décrets revêtent d’une nature judiciaire, ainsi le pouvoir judicaire du président de la république s’intensifie à travers ces juridictions exceptionnelles